A Comparative Study of the Seismic Performance of RC Buildings with Vertical Irregularity Using RC and GFRP Shear Walls - Chaudhary, Arjun; Khatri, Govinda; Shahi, Surendra Bahadur (Himalayan Journal of Applied Science and Engineering, 2026)
As per seismic studies, vertical irregular RC buildings show major weakness in earthquake areas. Regarding structural behaviour, geometry breaks increase side forces during ground shaking. Moreover, this study actually examines how G+10 RC buildings with setback irregularities perform during earthquakes, focusing on RC and GFRP shear walls. The study definitely determines which type of shear wall works better for these irregular building shapes. Moreover, a total of 4 models with different setback configurations were developed in ETABS software. Further, Response Spectrum Analysis was used to find the peak responses when the structure itself experiences seismic forces. The critical setback configuration was identified, and the optimum shear wall location was taken at corners only from the earlier study. As per the critical cases, a comparative study was conducted regarding conventional RC shear wall and GFRP reinforced shear wall. Both types were compared to find the differences. Results show that the RC shear walls actually made buildings much stiffer and reduced displacement by up to 42.324% and drift by up to 47.708%. GFRP shear walls definitely reduced displacement by up to 39.569% and drift by up to 44.798%, but RC walls actually handled more base force because they were stiffer. The findings highlight the trade-offs between RC and GFRP shear walls and provide practical insights into selecting an appropriate shear wall in irregular high-rise buildings.